Trade openness and bank risk-taking behavior: Evidence from emerging economies - Badar Nadeem Ashraf; Sidra Arshad; Liang Yan (Journal of Risk and Financial Management, 2017)
In this paper, we examine the impact of trade openness on bank risk-taking behavior. Using a panel dataset of 291 banks from 37 emerging countries over the period from 1998 to 2012, we find that higher trade openness decreases bank risk-taking. The results are robust when we use alternative bank risk-taking proxies and alternative estimation methods. We argue that trade openness provides diversification opportunities to banks in lending activities, which decrease overall bank risk. Further to this end, we observe that higher trade openness helps domestic banks to smooth out income volatility and decreases the impact of a financial crisis on banks.
Keywords: 650; trade openness; bank risk-taking; financial crisis; Z-score